High efficiency stable inverted perovskite solar cells without current hysteresis1. Issue 9 (26th September 2015) - Wu, Chun-Guey; Chiang, Chien-Hung; Tseng, Zong-Liang; Nazeeruddin, Md. K.; Hagfeldt, Anders; Grätzel, Michael
<x xml:space="preserve">Abstract</x> The inverted CH3NH3PbI3 cell fabricated using a two-step method with H2O as an additive in a PbI2 solution exhibited an extremely high FF of 85%.